PERBANYAKAN TANAMAN MELON (CUCUMIS MELO L.) SECARA IN VITRO PADA MEDIUM MS DENGAN PENAMBAHAN INDOLE ACETIC ACID (IAA) DAN BENZIL AMINO PURIN (BAP) - Lidyawati, Ni Nyoman; Waeniati, Waeniati; Muslimin, Muslimin; Suwastika, I Nengah (Univ. Tadulako, 2012)
The research on organogenesis of melon (Cucumis melo L.) was done at Tissue Culture Laboratory Forestry Faculty UNTAD Palu, during January until May 2012. The aim of this research was to determine the best concentration of IAA and BAP hormones in inducing organs of this plant. Sterile seedling of melon was used as explants in this work. The experiment was arranged in Completely Randomized Design (CRD) with 4 treatments and 4 replications. The treatments were MS0 + 0,1 ppm IAA + 0,5 ppm BAP (M1), MS0 + 0,1 ppm IAA + 0,7 ppm BAP (M2), MS0 + 0,1 ppm IAA + 0,9 ppm BAP (M3) and MS0 + 0,1 ppm IAA + 1 ppm BAP (M4). Parameters observed on this study were the day appear of shoot and leaves, the number of shoots and leaves and also the present of callus and root. The result showed that the best medium for organs induction was MS0 + 0,1 ppm IAA + 1 ppm BAP, which shoot and leaf emerged in the day of 3,75 and 5,75 after induction, respectively. This media was also induced the number of shoots and leaves, i.e 4,75 and 8,75, respectively. Nevertheles this media was not suitable enough in inducing root formation.